THE BALTIC VERBAL ROOTS* lV̄̆g-,* lV̄̆ź - Young, Steven (LU Academic, 2021)
The present paper attempts to shed additional light on a number of etymologies proposed for various Baltic (and related Slavic) verbal bases of the shape *lV̄̆g-, *lV̄̆ź-. These include *leg-, *leź-, *lēg-, *lēź-, together with their ablaut derivatives, and reflect a range of meanings, among them ‘lie (down); abate, subside (of weather, emotions); thaw; flat; crawl; fall ill’.
Keywords: baltic verbs; derivatives; *lV̄̆g-, *lV̄̆ź-; baltic verbal roots; meanings